Corticospinal excitability after 5-day Dry Immersion in women - Nosikova, Inna; Riabova, Alexandra; Kitov, Vladimir; Tomilovskaya, Elena (Frontiers in Neural Circuits, 2023)
In light of the development of manned astronautics and the increasing participation of women in space flights, the question of female body adaptation to microgravity conditions becomes relevant. Currently, one of the important directions in this issue is to study the effects of support withdrawal as a factor of weightlessness on human sensorimotor system. Dry Immersion is one of the well-known ground-based models, which adequately reproduces the main physiological effects of space flight. The aim of our work was to study changes in motor evoked potentials of the lower leg gravitydependent muscles in women after 5-day Dry Immersion. We analyzed evoked responses to transcranial and trans-spinal magnetic stimulation. In this method, areas of interest (motor cortex and lumbosacral thickening of the spinal cord) are stimulated with an electromagnetic stimulus. The experiment was conducted with the participation of 16 healthy female volunteers with a natural menstrual cycle. The thresholds, amplitudes, and latencies of motor potentials evoked by magnetic stimulation were assessed. We showed that 5-day exposure to support withdrawal leads to a decrease in motor evoked potentials thresholds and central motor conduction time, although changes in motor responses amplitudes were ambiguous. The data obtained correspond to the results of the previous research on Dry Immersion effects on sensorimotor system in men.